Automatic Surveillance System Triggered by Motion Detection and Android Notification - Widiyanto, Andi; Muhammad Pandam Taryono (IndoCompt Publisher, 2025)
Installation of Closed Circuit Television(CCTV) aims to monitor the conditions and situations of certain places as a step to prevent unwanted things. Conventional CCTV requires continuous monitoring and can not send user notifications in case of movement. In quiet areas, CCTV still records the same image for a very long time, making it ineffective, thus consuming storage space. In this study, the CCTV surveillance system uses motion detection sensors and will update the status of the Firebase database so that the Android application can display notifications. The movement that occurs will be detected by the PIR (Passive Infrared) sensor then will send a command to the Raspberry Pi to capture image and also send the sensor status on the firebase. Changes in sensor status will be listened to by the android application and if the sensor status changes android will notify the user that motion has just been detected. The test results show that the surveillance system can run well. The percentage of incoming notifications is compared with the detected motion with 80% results, the detection range is between 40-140 degrees, the detected motion delay is 2,055 seconds, the notification delay that goes to the user is 1.101 seconds